What is the current status of care by neuro-otology specialists in Switzerland—A national survey - Zwergal, Andreas; Mantokoudis, Georgios; Heg, Dik; Kerkeni, Hassen; Diener, Suzie; Kalla, Roger; Korda, Athanasia; Candreia, Claudia; Welge-Lüssen, Antje; Tarnutzer, Alexander A. (Frontiers in Neurology, 2023)
Background: Vertigo and dizziness are frequent presenting symptoms in the emergency department and in outpatient centers. While the majority of dizzy patients are evaluated by primary care physicians, specialists get often involved in the diagnostic workup. We aimed to gain more insights into the role of specialists in the care of the dizzy patient. Materials and methods: Board-certified neurologists and ear-nose-throat (ENT)-physicians working in Switzerland were invited to participate in an online survey. Descriptive statistical analyses were performed and prospectively defined hypotheses were assessed using correlation analyses. Results: All 111 participating specialists (neurologists=62; ENT-specialists=49) were familiar with testing for posterior-canal benign paroxysmal positional vertigo (BPPV) and 66% regularly applied provocation maneuvers for suspected lateral-canal BPPV. Reposition maneuvers for posterior (99%) and lateral (68%) canals were frequently performed. ENTphysicians were familiar with lateral-canal BPPV repositioning maneuvers significantly more often than neurologists (84% vs. 56%, p≤ 0.012). Specialists strongly agreed that performing the head-impulse test (86%) and looking for deficient eccentric gaze-holding (82%) is important. Compared to neurologists, significantly fewer ENT-physicians indicated ordering brain-MRI in acutely dizzy patients (OR=0.33 [0.16-0.067], p=0.002) and physical therapy in patients with acute (50% vs. 20%, p=0.005) or episodic/chronic dizziness (78% vs. 50%, p=0.003). Conclusions: We found substantial differences in the care of dizzy patients by neurologists and ENT-physicians. This underlines the need for a standardized, guideline-oriented diagnostic workup and treatment across specialties. Dedicated training for performing lateral-canal BPPV repositioning maneuvers should be prioritized in neurologists. Likewise physical therapy should be considered more often by ENT-physicians.